TINJAUAN YURIDIS ATAS KEWAJIBAN INVESTASI SAHAM PERUSAHAAN PENANAMAN MODAL ASING (PMA) DI BIDANG PERTAMBANGAN BATU BARA DI SAMARINDA BERDASARKAN UU NO. 25 TAHUN 2007 - Jupri Jupri (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT In the implementation of National Development , foreign investment has the role and position are very important for businesses as well as the center area . For foreign capital investment in the field of mining , especially PT . United Coal - Samarinda -based Housing Jl.DIPanjaitan . Citraland City office for the I -walk Blue Lane N0.01 in accordance with the legislation in force by the Chairman of BKPM ( Investment Coordinating Board ) on the basis of the Contract of Work . Foreign investment company that is run for the whole or part in Indonesia as a separate business unit to be incorporated Indonesian law and domiciled in Indonesia . PT . United Coal - Samarinda has been established in accordance with the terms of the shape , position and area trying applicable , all of the capital is foreign , must provide opportunities for participation by national capital effectively after a certain period of time and according to the balance prescribed by the Government . In fact , the efforts that have been made both Local and Central Government can not be fully implemented in our own strength . Various well as : capital accumulation has not been effective and efficient , Skills ( skills) , and management capabilities are not yet sufficient technology often creates a potential conflict between the needs of the real economic power by using funds derived from domestic and from abroad